Inclusive growth in Africa: Do fiscal measures matter? - Suleiman O. Mamman; Kazi Sohag; Attahir Babaji Abubakar (Cogent Economics & Finance, 2023)
In recent times, Africa has experienced remarkable economic growth; nonetheless, this advancement remains far from being considered inclusive, given the persistently high levels of poverty and income inequality across the continent. To this end, this study investigates the role of fiscal policy measures on inclusive growth using absolute and relative pro-poor measures of growth. The study utilizes panel data from 48 African countries spanning the period 1996 to 2020 and employs the Panel System Generalized Method of Moments (GMM) technique for analysis. Estimation results reveal a concerning trend where public debt service exacerbates both poverty and income inequality, underscoring the adverse consequences of mounting public debt pressures in the region. Interestingly, while government expenditure reduces inequality and worsens poverty, an increase in taxation reduces poverty but worsens income inequality. Further, an increase in taxation negatively affects the income shares of the bottom and middle-income groups while the top-income groups benefit. The findings of this study have significant policy implications for improving inclusive growth in the continent.
Keywords: E25; E62; H24; H25; I32; 330; Africa; debt service; fiscal policy; government expenditure; inclusive growth; income inequality; poverty; sustainable growth; taxation